Endothelial heterogeneity in the umbilico-placental unit: DNA methylation as an innuendo of epigenetic diversity - Casanello, Paola; Schneider, Daniela; Herrera, Emilio A.; Uauy, Ricardo; Krause, Bernardo J. (Frontiers in Pharmacology, 2014)
The endothelium is a multifunctional heterogeneous tissue playing a key role in the physiology of every organ. To accomplish this role the endothelium presents a phenotypic diversity that is early prompted during vascular development, allowing it to cope with specific requirements in a time- and site-specific manner. During the last decade several reports show that endothelial diversity is also present in the umbilico-placental vasculature, with differences between macro- and microvascular vessels as well as arterial and venous endothelium. This diversity is evidenced in vitro as a higher angiogenic capacity in the microcirculation; or disparity in the levels of several molecules that control endothelial function (i.e. receptor for growth factors, vasoactive mediators and adhesion molecules) which frequently are differentially expressed between arterial and venous endothelium. Emerging evidence suggests that endothelial diversity would be prominently driven by epigenetic mechanisms which also control the basal expression of endothelial-specific genes. This review outlines evidence for endothelial diversity since early stages of vascular development and how this heterogeneity is expressed in the umbilico-placental vasculature. Furthermore a brief picture of epigenetic mechanisms and their role on endothelial physiology emphasising new data on umbilical and placental endothelial cells is presented. Unravelling the role of epigenetic mechanisms on long-term endothelial physiology and its functional diversity would contribute to develop more accurate therapeutic interventions. Altogether these data show that micro- versus macro-vascular, or artery versus vein comparisons are an oversimplification of the complexity occurring in the endothelium at different levels, and the necessity for the future research to establish the precise source of cells which are under study.